A New Three-Parameter Lifetime Model: Properties and Applications - H. M. Abdelkhalek, Rania (Thailand Statistician, 2022)
A new three-parameter flexible version from the Nadarajah Haghighi model based on Lemonte (2013) is proposed and studied. Statistical properties of the new version are derived. A numerical analysis for the variance, skewness and kurtosis is presented as well as three-dimensional plots are sketched for discovering the flexibility of the new model. A simple type copula based construction is presented for deriving many bivariate and multivariate type distributions. Parameter estimates process are conducted by the well-known method of maximum likelihood. Numerical illustration of real data set is employed to compare the new model with other competitive models. A numerical simulations are executed to test performance of the used method.